New views on price-making markets and the capitalist impulse: beyond Polanyi - Blanton, Richard E.; Feinman, Gary M. (Frontiers in Human Dynamics, 2024)
Anthropologists have persistently diminished the importance of the market and marketplace exchange in premodern, preindustrial times. This strident anti-market mentality, derived largely from the writings of Karl Polanyi, underpins an ideological and politicized argument that neither sets useful guideposts to advance anthropological research, nor does it yield the necessary insights or empirically valid foundations to comprehend the deep historical origins of modern economies or polities. In fact, by envisioning the past that is categorically caged from the modern, the school of thought crystalized through Polanyi's perspectives circumvents the role of diachronic processes that are at the heart of a truly historical social science. Although it is not our principal aim to relitigate the vast literature pertaining to the rise and fall of Polanyian thought, our approach expands on prior arguments about his project both by highlighting critical perspectives on capitalism that long predated Polanyian thought and by identifying a veritable bounty of new evidence and theory concerning premodern and contemporary marketplace economies that enable us to transcend these now-entrenched claims. The scheme we present, that distinguishes between open and competitive marketplaces, on the one hand, and the capitalist impulse, on the other, we believe, adds depth and breadth to the analysis of price-making markets and their divergent social and economic outcomes across time and space.From their ethnographic observations of social exchange in small-scale societies, anthropologists realized that Western economic theory, with its deductive logical framework, its assumption that humans are consistently utility maximizers, its lack of concern with institutional variation, and its basic disinterest in long-term change, would be poorly suited to building a holistic discipline of economic anthropology. Although various directions for this new discipline were proposed, the approach developed by Karl Polanyi initially gained the most traction (e.g.